1998
DOI: 10.1074/jbc.273.5.2714
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Type I Interferon Gene Expression by Interferon Regulatory Factor-3

Abstract: Viral infection leads to the transient expression of early inflammatory genes. The proteins encoded by these genes enhance recognition of the infected cells by the host immune system. A group of proteins, called interferons (IFNs), 1 can directly inhibit viral replication. Type I IFNs are encoded by a family of closely related ␣ genes and a single IFNB gene, which are all localized on chromosome 9 (1, 2). The sequences that regulate inducible transcription of these genes are localized within the 100-nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
219
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(230 citation statements)
references
References 55 publications
(56 reference statements)
8
219
1
2
Order By: Relevance
“…Inhibition of PI3K activity enhances poly(I:C)-and LPS-mediated NF-jB but not IRF3 activation in DC IFN-b gene expression requires cooperation between NF-jB [28,29] and IRF3 [30][31][32] transcription factors. Therefore, we quantified the levels of NF-jB and IRF3 DNA-binding activities in nuclear extracts from wortmannin-treated DC versus control counterparts following LPS or poly(I:C) stimulation.…”
Section: Pi3k Inhibition Enhances Ifn-b Synthesis In DC Stimulated Bymentioning
confidence: 97%
“…Inhibition of PI3K activity enhances poly(I:C)-and LPS-mediated NF-jB but not IRF3 activation in DC IFN-b gene expression requires cooperation between NF-jB [28,29] and IRF3 [30][31][32] transcription factors. Therefore, we quantified the levels of NF-jB and IRF3 DNA-binding activities in nuclear extracts from wortmannin-treated DC versus control counterparts following LPS or poly(I:C) stimulation.…”
Section: Pi3k Inhibition Enhances Ifn-b Synthesis In DC Stimulated Bymentioning
confidence: 97%
“…TRAF3) and IFN regulatory factors (IRF3, 7) join with nuclear factor-kappabeta to stimulate the IFNB (and alpha) promoters within the nucleus [10]. Once produced, IFNB acts through the IFN alpha/beta receptor (IFNAR) found on many cell types.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…The effects of IFN-␥ are mediated through the formation of Stat1␣ dimers that bind to GAS motifs. [41][42][43] The role of type I IFNs in the activation of macrophages has been a subject of controversy. Some investigators reported a potentiation of the activation process, 37,44 and others described an anti-inflammatory contribution.…”
Section: Figure 7 Ifn-␥ Signaling Is Altered In Mice Expressing Hifn-mentioning
confidence: 99%